PENGARUH JENIS MINYAK NABATI TERHADAP NILAI KALOR BIODIESEL HASIL TRANSESTERIFIKASI DENGAN KATALIS KOH - Aan Candra Ajis, Aan Candra Ajis; Asroful Abidin; Mokh. Hairul Bahri (Lembaga Pengembangan Kinerja Dosen, 2025)
The research utilizes three types of oil, namely used cooking oil, candlenut oil, and olive oil, which were selected due to their availability and potential as biodiesel feedstocks. The main issue addressed in this study is the high dependence on fossil fuels and the need for renewable energy sources with sufficient energy content. This research aims to compare the calorific values of biodiesel produced from different vegetable oils to determine their potential as alternative fuels. Biodiesel was produced through a transesterification process using methanol with a methanol-to-oil ratio of 6:1 and 1% KOH catalyst by weight of oil. The calorific value of the biodiesel was measured using a bomb calorimeter. The results show that biodiesel derived from candlenut oil has the highest calorific value of 8037.07 Cal/gram, followed by biodiesel from used cooking oil at 7399.07 Cal/gram, while biodiesel from olive oil has the lowest calorific value of 7295.15 Cal/gram. These results indicate that the type of vegetable oil significantly influences the calorific value of biodiesel. In conclusion, candlenut oil has the greatest potential as a biodiesel feedstock based on its higher energy content compared to used cooking oil and olive oil.